Varieties of regulation: how states pursue and set international financial standards - Prabhakar, R (2013)
What explains the form and substance of international financial standards? Form refers to the legal or non-legal bindingness of an international standard. Substance refers to how significantly the standard changes the international status quo. The form and substance of international standards on bank capital adequacy, hedge funds, “bail-in” resolution, and insurance capital adequacy challenge the predictions of major rationalist, realist, and two-level perspectives. I propose a novel theory and present original evidence to test two central claims. First, the structure of domestic institutions and strategic interaction within a state incentivizes an actor from that state to prefer and pursue a certain form of international standard: legally or non-legally binding. The state actor, as a first mover, aims to propose a standard at an appropriate international institution which produces standards of its preferred form. Second, the state actor must bargain with representatives of other states according to certain decision-making rules at the international standard-setting institution. The type of decision-making rule used in bargaining—not the market power or other characteristics of key players—explains the substance of the final standard. More restrictive decision-making rules, which use majority or supermajority voting, lead to greater change than open rules, which are based on consensus or unanimity voting. My empirical findings remove the veneer of technocratic legitimacy associated with international standard-setting to reveal intense distributional battles. In pursuing the Basel capital standards, the US Federal Reserve has been motivated more by turf wars with other US bank regulators than by its publicly stated desire to create a “level playing field” for internationally active banks. Supported by domestic collaboration between regulators and industry, French officials set a legally binding and deep de facto international standard for hedge fund managers over the vigorous objections of the City of London. By pursuing a soft standard on bail-in, the Bank of England has sought not only to protect taxpayers from costly bailouts, but also to keep Her Majesty’s Treasury at arm’s length. The lack of international insurance regulation is due not to the lack of effort by the UK Financial Services Authority and its European partners, but to open decision-making rules that allow US state regulators, albeit fragmented and under-resourced, to protect the international status quo. In each of these cases, I specify how domestic and international institutional settings provide enduring opportunities and constraints for key players in global finance.